IDEAL study: magnetic resonance imaging for suspected deep endometriosis assessment prior to laparoscopy is as reliable as radiological imaging as a complement to transvaginal ultrasonography. (27th June 2020) - Bielen, D.; Tomassetti, C.; Van Schoubroeck, D.; Vanbeckevoort, D.; De Wever, L.; Van den Bosch, T.; D'Hooghe, T.; Bourne, T.; D'Hoore, A.; Wolthuis, A.; Van Cleynenbreughel, B.; Meuleman, C.; et al.
ABSTRACT: Objective: To compare the value of using one‐stop magnetic resonance imaging (MRI) vs standard radiological imaging as a supplement to transvaginal ultrasonography (TVS) for the preoperative assessment of patients with endometriosis referred for surgery in a tertiary care academic center. Methods: This prospective observational study compared the diagnostic value of the standard preoperative imaging practice of our center, which involves expert TVS complemented by intravenous urography (IVU) for the evaluation of the ureters and double‐contrast barium enema (DCBE) for the evaluation of the rectum, sigmoid and cecum, with that of expert TVS complemented by a 'one‐stop' MRI examination evaluating the upper abdomen, pelvis, kidneys and ureters as well as rectum and sigmoid on the same day, for the preoperative triaging of 74 women with clinically suspected deep endometriosis. The findings at laparoscopy were considered the reference standard. Patients were stratified according to their need for monodisciplinary surgical approach, carried out by gynecologists only, or multidisciplinary surgical approach, involving abdominal surgeons and/or urologists, based on the extent to which endometriosis affected the reproductive organs, bowel, ureters, bladder or other abdominal organs. Results: Our standard preoperative imaging approach and the combined findings of TVS and MRI had similar diagnostic performance, resulting in correct stratification for a monodisciplinary or a multidisciplinary surgical approach of 67/74 (90.5%) patients. However, there were differences between the estimation of the severity of disease by DCBE and MRI. The severity of rectal involvement was underestimated in 2.7% of the patients by both TVS and DCBE, whereas it was overestimated in 6.8% of the patients by TVS and/or DCBE. Conclusions: Complementary to expert TVS, 'one‐stop' MRI can predict intraoperative findings equally well as standard radiological imaging (IVU and DCBE) in patients referred for endometriosis surgery in a tertiary care academic center. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.